The Development Concept of the Integrated Electronic Detonator - Paul N. Worsey; Lawson J. Taylor (International Society of Explosives Engineers, 1983)
Recent reputable evidence conclusively indicates that conventional chemical delay elements in delay detonators are notoriously inaccurate and can thus seriously affect blasting efficiency.